2022
DOI: 10.1021/acs.jmedchem.1c01585
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of HDAC6-Selective Inhibitor NN-390 with in Vitro Efficacy in Group 3 Medulloblastoma

Abstract: Histone deacetylase 6 (HDAC6) has been targeted in clinical studies for anticancer effects due to its role in oncogenic transformation and metastasis. Through a second-generation structure–activity relationship (SAR) study, the design, and biological evaluation of the selective HDAC6 inhibitor NN-390 is reported. With nanomolar HDAC6 potency, >200–550-fold selectivity for HDAC6 in analogous HDAC isoform functional assays, potent intracellular target engagement, and robust cellular efficacy in cancer cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 81 publications
0
25
0
Order By: Relevance
“…Ricolinostat and Citarinostat (Figure 3) are hydroxamates, which are quite selective toward the Class-II HDAC6 (HDAC1/HDAC6 selectivity index = 13 and 12, respectively) and are under evaluation against different malignancies [15,16]. In general, new and more selective HDAC6 inhibitors have been disclosed as useful tools to counteract tumor progression [17,18], although it was also reported that the selective inhibition of HDAC6 is not necessarily related to an anticancer activity, as observed for Tubathian A (Figure 3) and related compounds [19]. Therefore, increasing attention is required for the evaluation of HDAC inhibitors as anticancer drugs, especially when used as single agents.…”
Section: Pharmacophoric Model Of Hdac Inhibitorsmentioning
confidence: 99%
“…Ricolinostat and Citarinostat (Figure 3) are hydroxamates, which are quite selective toward the Class-II HDAC6 (HDAC1/HDAC6 selectivity index = 13 and 12, respectively) and are under evaluation against different malignancies [15,16]. In general, new and more selective HDAC6 inhibitors have been disclosed as useful tools to counteract tumor progression [17,18], although it was also reported that the selective inhibition of HDAC6 is not necessarily related to an anticancer activity, as observed for Tubathian A (Figure 3) and related compounds [19]. Therefore, increasing attention is required for the evaluation of HDAC inhibitors as anticancer drugs, especially when used as single agents.…”
Section: Pharmacophoric Model Of Hdac Inhibitorsmentioning
confidence: 99%
“…Unlike other HDACs, the development of HDAC6-specific inhibitors has been relatively successful [ 6 , 7 , 47 ]. NN-390, the first HDAC6-selective inhibitor, has shown therapeutic potential for Group 3 medulloblastoma (MB), an aggressive pediatric brain tumor associated with leptomeningeal metastases and therapy resistance [ 48 ]. NM-390 targets MB stem cells and demonstrates a 45-fold increased efficacy over HDAC6 inhibitor citarinostat (ACY-241) [ 48 ].…”
Section: Hdac6-selective Inhibitorsmentioning
confidence: 99%
“…NN-390, the first HDAC6-selective inhibitor, has shown therapeutic potential for Group 3 medulloblastoma (MB), an aggressive pediatric brain tumor associated with leptomeningeal metastases and therapy resistance [ 48 ]. NM-390 targets MB stem cells and demonstrates a 45-fold increased efficacy over HDAC6 inhibitor citarinostat (ACY-241) [ 48 ]. ACY-1215 was shown to inhibit the translocation of GRP78 to the plasma membrane by inhibiting the PI3K/AKT signaling [ 47 ].…”
Section: Hdac6-selective Inhibitorsmentioning
confidence: 99%
“…The synthetic pathway used to furnish NN-429 is outlined in Scheme 1. Synthesis of NN-390 has been previously described [27]. Tert-butyl ester protection of 3-fluoro-4-methylbenzoic acid (1) led to the generation of tert-butyl 3-fluoro-4-methylbenzoate (2, 70%), which was then brominated at the benzylic position (3, 56%).…”
Section: Chemistrymentioning
confidence: 99%
“…Given these clinical needs, particularly for the incurable, aggressive, and rare entities of γδ T-NHL and NKTCLs, we aimed to design an HDAC6 inhibitor with drug-like properties, explored here via medicinal chemistry, X-ray crystallography studies, pharmacological and biochemical methodologies. NN-429 is an improved analog of older generation HDAC6 inhibitor molecules KT-531 and NN-390, with higher in vitro selectivity, target potency and in vivo half-life [10,27]. We specifically studied our novel HDAC6 inhibitor, NN-429, in a panel of human PTCL cell lines to explore targeted drug efficacy, finding the highest sensitives in hepatosplenic γδ T-NHL and NKTCL derived cell lines.…”
Section: Introductionmentioning
confidence: 99%